Effect of an antimicrobial stewardship programme on antimicrobial utilisation and costs in patients with leukaemia: a retrospective controlled study. (August 2018) - So, M.; Mamdani, M.M.; Morris, A.M.; Lau, T.T.Y.; Broady, R.; Deotare, U.; Grant, J.; Kim, D.; Schimmer, A.D.; Schuh, A.C.; Shajari, S.; Steinberg, M.; et al.
Abstract: Objectives: To examine the effectiveness of an antimicrobial stewardship programme on utilization and cost of antimicrobials in leukaemia patients in Canada. Methods: We conducted a multisite retrospective observational time series study from 2005 to 2013. We implemented academic detailing as the intervention of an antimicrobial stewardship programme in leukaemia units at a hospital, piloted February–July 2010, then fully implemented December 2010–March 2013, with no intervention in August–November 2010. Internal control was the same hospital's allogeneic haematopoietic stem-cell transplantation unit. External control was the combined leukaemia–haematopoietic stem-cell transplantation unit at another hospital. Primary outcome was antimicrobial utilization (antibiotics and antifungals) in defined daily dose per 100 patient-days (PD). Secondary outcomes were antimicrobial cost (Canadian dollars per PD); cost and utilization by drug class; length of stay; 30-day inpatient mortality; and nosocomial Clostridium difficile infection. We used autoregressive integrated moving average models to evaluate the impact of the intervention on outcomes. Results: The intervention group included 1006 patients before implementation and 335 during full implementation. Correspondingly, internal control had 723 and 264 patients, external control 1395 and 864 patients. Antimicrobial utilization decreased significantly in the intervention group (p <0.01, 278 vs. 247 defined daily dose per 100 PD), increased in external control (p = 0.02, 237.4 vs. 268.9 defined daily dose per 100 PD) and remained stable in internal control (p = 0.66). Antimicrobial cost decreased in the intervention group (p = 0.03; 154.59 per PD vs. 128.93 per PD), increased in external control (p = 0.01; 109.4 per PD vs. 135.97 per PD) but was stable in internal control (p = 0.27). Mortality, length of stay and nosocomial C. difficile rate in intervention group remained stable. Conclusions: The antimicrobial stewardship programme reduced antimicrobial use in leukaemia patients without affecting inpatient mortality and length of stay.